Experimental Study Of InGaP/GaAs DHBTS With Composite Collector - Poh, Zi-Song (2009)
This thesis presents an experimental study of composite collector InGaP/GaAs Double Heterojunction Bipolar Transistors (DHBTs) grown by metal organic vapour phase epitaxy (MOVPE). InGaP/GaAs/InGaP double heterojuntion bipolar transistor (DHBT) incorporating dead space corrected GaAs-InGaP composite collector is investigated experimentally.